2010
DOI: 10.1001/archgenpsychiatry.2010.147
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia and Other Psychotic Disorders in a Cohort of Sexually Abused Children

Abstract: Child sexual abuse involving penetration is a risk factor for developing psychotic and schizophrenic syndromes. The risk is greater for adolescents subjected to penetration. Irrespective of whether this statistical association reflects any causal link, it does identify an at-risk population in need of ongoing support and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
132
2
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(147 citation statements)
references
References 32 publications
(27 reference statements)
7
132
2
4
Order By: Relevance
“…Repeated exposure to severe stress in critical developmental stages, especially during the early childhood, may disrupt PFC development and impair working memory later in life (Evans and Schamberg, 2009;Hanson et al, 2012). Accumulating evidence demonstrates that early-life stress is one of the major risk factors for psychiatric disorders, including schizophrenia, depression, and anxiety disorders (Bradley et al, 2008;Cutajar et al, 2010;Nugent et al, 2011) that are associated with prefrontal dysfunction (Goto et al, 2010) and structural abnormalities (Black et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Repeated exposure to severe stress in critical developmental stages, especially during the early childhood, may disrupt PFC development and impair working memory later in life (Evans and Schamberg, 2009;Hanson et al, 2012). Accumulating evidence demonstrates that early-life stress is one of the major risk factors for psychiatric disorders, including schizophrenia, depression, and anxiety disorders (Bradley et al, 2008;Cutajar et al, 2010;Nugent et al, 2011) that are associated with prefrontal dysfunction (Goto et al, 2010) and structural abnormalities (Black et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There is a robust research foundation that has demonstrated a relationship between adverse childhood experience (poverty, neglect, maltreatment, physical, sexual, and psychological abuse) and development of an array of mental disorders (Beardslee, Chien, and Bell 2011;Fitzsimons et al 2016;Tillfors et al 2009;Hoeve et al 2015;Kelleher et al 2013;Cutajar et al 2010;Kelleher et al 2013;DaruyFilho et al 2011). It is abundantly clear that such social pathologies are good for no one's mental health.…”
Section: Anxiety and The Role Of Resiliencementioning
confidence: 99%
“…these factors may predict shifts upwards the psychosis continuum along the full spectrum. Many studies have shown the role of (psychological, physical and sexual) trauma during childhood and adolescence in the development of psychosis and psychotic symptoms/experiences (Arseneault et al, 2011;Cutajar et al, 2010;Fisher et al, 2010;Introduction 2004b;Verdoux, Sorbara et al, 2002), urbanicity (Spauwen, Krabbendam, Lieb, Wittchen, & van Os, 2004;Spauwen et al, 2006a;Stefanis, Delespaul, Smyrnis et al, 2004) and ethnic minority status . Recently, the concept of 'social defeat' has been introduced.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…For example, one study reported the strongest associations for exposure before the age of 12 years (Fisher et al, 2010), others for exposure after age 12 years (Cutajar et al, 2010) and yet others did not find evidence for effect modification by age (Arseneault et al, 2011;Spauwen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation